Capability-Based Pathways to Performance: The Mediating Role of Resilience and Value Realization in Agri-Supply Chains - Retno Setyorini; Agus Rahayu; Lili Adi Wibowo; Mokh. Adib Sultan (Jurnal Ilmiah Manajemen Kesatuan, 2025)
Global agribusiness faces increasing volatility and disruptions, making supply chain performance critical for competitiveness, especially in developing economies where structural fragmentation and limited adaptive capacity hinder value creation. This study investigates how strategic agility enhances supply chain performance through the mediating roles of supply chain resilience and value realization among millennial coffee farmers in West Java, Indonesia. A quantitative explanatory design was employed, collecting data from 143 coffee farmers selected through purposive sampling. Covariance-Based Structural Equation Modeling was used to analyze direct and sequential relationships among constructs. Findings show that strategic agility positively influences supply chain resilience  and value realization, with resilience mediating the relationship between agility and value realization, and value realization driving performance. The sequential mediation pathway from agility through resilience and value realization to performance is significant. This study validates an integrated capability-based model, offering practical insights for enhancing adaptive capacity and competitiveness in agribusiness supply chains. Future research should explore longitudinal effects and broader agribusiness contexts to strengthen generalizability.